METODE ISTISHLAH, URF DAN QIYAS DALAM PENETAPAN HARTA BERSAMA PERKAWINAN PADA KOMPILASI HUKUM ISLAM - Noor, Dzulkifli (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
Joint property is a law that regulates joint assets obtained during marriage between husband and wife in the event of the death of one party or divorce. The common property law is adopted from Indonesian common law (adat law), which has been used by all ethnic groups in Indonesian society since time immemorial. As the law recognized all of the ethnic in the Indonesian peoples, distribution joint property in common laws of the ethnic is variety. The government need to unificate the varieties becomes the unification law and positive laws in Indonesia. The existence joint property after unification law is in the Law on Marriage No. 1 year 1974. The detail implementing regulation of joint property for the moslem court is the instruction of president No. 1 year 1991 about compilation of Islamic laws. The existence of joint property in the perspective of Islamic law is the result of the ijtihad of Jamai Ulama in Indonesia, which relies on the legal determination of the ushul fiqh method, namely the istishlah and urf methods.Joint property is a law that regulates joint assets obtained during marriage between husband and wife in the event of the death of one party or divorce. The common property law is adopted from Indonesian common law (adat law), which has been used by all ethnic groups in Indonesian society since time immemorial. As the law recognized all of the ethnic in the Indonesian peoples, distribution joint property in common laws of the ethnic is variety. The government need to unificate the varieties becomes the unification law and positive laws in Indonesia. The existence joint property after unification law is in the Law on Marriage No. 1 year 1974. The detail implementing regulation of joint property for the moslem court is the instruction of president No. 1 year 1991 about compilation of Islamic laws. The existence of joint property in the perspective of Islamic law is the result of the ijtihad of Jamai Ulama in Indonesia, which relies on the legal determination of the ushul fiqh method, namely the istishlah and urf methods.